Peningkatan Literasi Digital Melalui Pelatihan Microsoft Office dan Internet Sehat Bagi Remaja - Kristanto, Titus; Priawan Siregar, Aslam Chitami (Abdimas Mandalika, 2026)
Abstract: The development of information technology requires the younger generation to have adequate digital literacy skills to utilize it productively and responsibly. However, some teenagers in Kertajaya Village, Surabaya City, still lack knowledge on how to use office applications and how to use the internet healthily. Therefore, community service activities aim to improve adolescent digital literacy through Microsoft Office and healthy internet use. The community service activity method involves several stages: identifying partner problems, coordinating with the village, creating training modules, implementing training, accompanying participants, and monitoring and evaluating activities. The training activities involved 20 teenagers from junior high and high schools in Kertajaya Village through counseling, demonstrations, direct practice, and mentoring. The results of the activities showed that participants understood how to use Microsoft Word and Microsoft Excel applications and found wise and healthy ways to use the internet. Participants also showed increased confidence in using digital technology to support learning. Overall, the training activities successfully improved participants' digital literacy, both in terms of technical skills and awareness of using the internet productively and positively.Abstrak: Perkembangan teknologi informasi menuntut generasi muda memiliki kemampuan literasi digital yang memadai agar dapat memanfaatkan teknologi secara produktif dan bertanggungjawab. Namun, beberapa remaja di Kelurahan Kertajaya, Kota Surabaya, masih kekurangan pengetahuan tentang cara menggunakan aplikasi perkantoran dan cara menggunakan internet sehat. Oleh karena itu, kegiatan pengabdian masyarakat bertujuan untuk meningkatkan literasi digital remaja melalui Microsoft Office dan penggunaan internet sehat. Metode kegiatan pengabdian melalui beberapa tahap yaitu menemukan masalah mitra, koordinasi dengan pihak kelurahan, membuat modul pelatihan, melaksanakan pelatihan, mendampingi peserta, monitoring dan evaluasi kegiatan. Kegiatan pelatihan melibatkan 20 remaja dari SMP dan SMA di Kelurahan Kertajaya melalui penyuluhan, demonstrasi, praktik langsung, dan pendampingan. Hasil kegiatan menunjukkan bahwa peserta memahami menggunakan aplikasi Microsoft Word dan Microsoft Excel, serta memahami cara bijak dan sehat dalam menggunakan internet. Peserta juga menunjukkan peningkatan kepercayaan diri dalam menggunakan teknologi digital untuk membantu pembelajaran. Secara keseluruhan, kegiatan pelatihan berhasil meningkatkan literasi digital peserta, baik dari segi keterampilan teknis maupun kesadaran menggunakan internet secara produktif dan positif.